(untitled) (Global Business Management Review (GBMR), 2021)
This study examines the cognitive factors that determine corporate environmental accounting disclosures (CEAD). The population consists of all the fourteen (14) listed oil and gas firms in Nigeria. Panel data were obtained from the annual reports and accounts of the firms for the period of 2010 to 2019. A correlational research design was used and the data were analyzed using the Generalized Least Square regression (random model). The study found that firm size; leverage and multi-national companies have positive significant influence on the CEAD of listed oil and gas firms in Nigeria. Whilst firm growth has a negative significant relationship with the CEAD of listed oil and gas firms in Nigeria. It is concluded that larger firms and multi-national companies in the Nigerian oil and gas sector have high likelihood of disclosing environmental accounting information. Thus, it is recommended that the management of listed oil and gas firms in Nigeria should expand their size by acquiring more assets, maintain a consistent growth by exploring more opportunities while improving their gearing ratio to ensure a stable balance between the proportion of debt and assets. It therefore, highlighted the need for Securities and Exchange Commission (SEC) to come up with enabling laws geared towards ensuring that listed oil and gas firms in Nigeria embrace CEAD. Furthermore, Global Environmental Disclosure Index (GEI) should be considered as the most acceptable yardstick for measuring environmental accounting by the listed oil and gas firms in Nigeria.